Type 2 familial hemophagocytic lymphohistiocytosis in half brothers: A case report. Issue 30 (July 2018) - Liu, Chunxia; Li, Ming; Wu, Xiaomei; Yao, Xiaojian; Zhao, Li
Abstract: Rationale: We describe a novel case of half-brothers suffering from type 2 familial hemophagocytic lymphohistiocytosis (FHL). Patient concerns: A 15-year-old Chinese child was admitted to the hematology department. PRF1 gene coding revealed that he was c.282C>A/p.N94K heterozygous and had a c.1349C>T/p.T450M heterozygous mutation. One year later, his younger halfbrother suffered from the same disease. PRF1 gene coding revealed that the younger brother was c.282C>A/p.T450M heterozygous with a c.1349C>T/p.T450M heterozygous mutation. His mother and grandfather were confirmed to have c.1349C>T/p.T450M heterozygous mutations in exon 3. Diagnoses: Half-brothers were diagnosed for type 2 familial hemophagocytic lymphohistiocytosis Interventions: To our knowledge, this is a possible FHL and the children's mother may be a pathogenic gene carrier. Outcomes: After being treated with the HLH-04 schedule, the symptoms of half-brothers were all improved. Lessons subsections: Therefore, once FHL is diagnosed, HSCT needs to be done early, even if no perfect match is found.